Expression Profiling and Functional Analysis of Circular RNAs in Inner Mongolian Cashmere Goat Hair Follicles - Shang, Fangzheng; Wang, Yu; Ma, Rong; Di, Zhengyang; Wu, Zhihong; Hai, Erhan; Rong, Youjun; Pan, Jianfeng; Liang, Lili; Wang, Zhiying; Wang, Ruijun; Liu, Zhihong; et al. (Frontiers in Genetics, 2021)
Background Inner Mongolian cashmere goats have hair of excellent quality and high economic value, and the skin hair follicle traits of cashmere goats have a direct and important effect on cashmere yield and quality. Circular RNA has been studied in a variety of tissues and cells. Result In this study, high-throughput sequencing was used to obtain the expression profiles of circular RNA (circRNA) in the hair follicles of Inner Mongolian cashmere goats at different embryonic stages (45, 55, 65, and 75 days). A total of 21,784 circRNAs were identified. At the same time, the differentially expressed circRNA in the six comparison groups formed in the four stages were: d75vsd45, 59 upregulated and 33 downregulated DE circRNAs; d75vsd55, 61 upregulated and 102 downregulated DE circRNAs; d75vsd65, 32 upregulated and 33 downregulated DE circRNAs; d65vsd55, 67 upregulated and 169 downregulated DE circRNAs; d65vsd45, 96 upregulated and 63 downregulated DE circRNAs; and d55vsd45, 76 upregulated and 42 downregulated DE circRNAs. Six DE circRNA were randomly selected to verify the reliability of the sequencing results by quantitative RT-PCR. Subsequently, the circRNA corresponding host genes were analyzed by the Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. The results showed that the biological processes related to hair follicle growth and development enriched by GO mainly included hair follicle morphogenesis and cell development, and the signaling pathways related to hair follicle development included the Notch signaling pathway and NF-κB signaling pathway. We combined the DE circRNA of d75vsd45 with miRNA and mRNA databases (unpublished) to construct the regulatory network of circRNA–miRNA–mRNA, and formed a total of 102 pairs of circRNA–miRNA and 126 pairs of miRNA–mRNA interactions. The binding relationship of circRNA3236–chi-miR-27b-3p and circRNA3236–chi-miR-16b-3p was further verified by dual-luciferase reporter assays, and the results showed that circRNA3236 and chi-miR-27b-3p, and circRNA3236 and chi-miR-16b-3p have a targeted binding relationship. Conclusion To summarize, we established the expression profiling of circRNA in the fetal skin hair follicles of cashmere goats, and found that the host gene of circRNA may be involved in the development of hair follicles of cashmere goats. The regulatory network of circRNA–miRNA–mRNA was constructed and preliminarily verified using DE circRNAs.